Dietary Patterns During Lactation and Human Milk Composition and Quantity: A NESR Systematic Review. (7th June 2021) - Scinto-Madonich, Sara; Donovan, Sharon M; Dewey, Kathryn; Novotny, Rachel; Stang, Jamie; Taveras, Elsie; Kleinman, Ronald; Raghavan, Ramkripa; Nevins, Julie; Kim, Julia; Butera, Gisela; Terry, Nancy; et al.
Abstract: Objectives: To inform the Dietary Guidelines for Americans, 2020–2025, the USDA and HHS identified important public health questions to be examined by the 2020 Dietary Guidelines Advisory Committee. The Committee conducted a systematic review with support from the USDA's Nutrition Evidence Systematic Review (NESR) team to answer the question: What is the relationship between dietary patterns consumed during lactation and human milk composition and quantity? Methods: The Committee developed protocols to describe how they would use NESR's SR methodology to examine the evidence related to dietary patterns (DP) during lactation and human milk (HM). NESR librarians conducted a literature search and NESR analysts dual-screened the results using pre-defined inclusion and exclusion criteria to identify articles published between 2000 and 2019. NESR analysts extracted data from and assessed the risk of bias of included studies. The Committee synthesized the evidence, developed conclusion statements, and graded the strength of the evidence. Results: This systematic review included 7 articles. Three articles from 2 cross-sectional studies examined DP and HM, while 4 articles from 3 randomized controlled trials examined diets based on macronutrient distributions and HM. The body of evidence was limited by small sample sizes, risk of bias concerns, heterogeneous methods, and study populations with limited racial/ethnic and socioeconomic diversity. Conclusions: Limited evidence suggests that maternal consumption of diets higher in fat (>35% fat) and lower in carbohydrate during lactation is related to higher total fat in HM collected in the maternal postprandial period. Limited evidence suggests that certain maternal DP during lactation, including diets based on macronutrient distributions, are related to the relative proportions of saturated fat and monounsaturated fatty acids in HM, and of polyunsaturated fatty acids in HM collected in the maternal postprandial period. Insufficient or no evidence was available to assess the association between DP during lactation and HM quantity, as well as total protein, water- and fat-soluble vitamins, minerals, human milk oligosaccharides, and bioactive proteins in HM. Funding Sources: USDA, Food and Nutrition Service, Center for Nutrition Policy and Promotion.